Customer satisfaction level with futsal field management services - Lestari, Ade Tuti; Ramadhan, Zulfi (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2022)
The purpose of this study was to determine the extent of consumer satisfaction with futsal field management services during the covid-19 pandemic in Serang City. The method used is the associative survey method and the sample used is all consumers who use futsal field services in Serang City by using incidental sampling, where in this study researchers will provide questionnaires to futsal field customers in 4 different fields in Serang City. The 4 fields are Radar Banten Arena (Serang District), KeneWae Futsal (Cipocok District), Blafut Futsal (Crug District) and Star Futsal (Walantaka District) with 41 people. The results of the study obtained from the distribution of questionnaires to consumers who use service obtained the level of customer satisfaction with the services provided by each futsal field manager in Serang City is in the category of dissatisfied with a percentage of 48%. The poor service can be shown by the incompleteness of existing facilities, cleanliness of the place, security, comfort and also the performance of the waiters who work in the place.Key words: Level of satisfaction, Consumers, Services